2008
DOI: 10.1017/s0007114508006521
|View full text |Cite
|
Sign up to set email alerts
|

Role of neonatal hyperleptinaemia on serum adiponectin and suppressor of cytokine signalling-3 expression in young rats

Abstract: Previously we had shown that neonatal leptin treatment programmes for both hyperleptinaemia and hyperinsulinaemia, which lead to leptin resistance and low expression of the hypothalamic leptin receptor (OB-Rb) of rats aged 150 d. Here we investigated in young post-weaned rats (age 30 d) if leptin treatment during lactation induces leptin and insulin resistance and if those changes are accompanied by changes in the suppressor of cytokine signalling-3 (SOCS-3) expression and serum adiponectin concentration. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 52 publications
9
18
0
Order By: Relevance
“…This result could explain the hyperphagia observed in adult overfed animals. In other models of programming during lactation, our group showed that leptin injections on the first 10 days of life program for hyperleptinemia when they were 30 days old, lower Ob-Rb and higher SOCS3 content in hypothalamus [63], similar to our present results for adult SL rats. As stated before, SOCS3 does an intracellular feedback regulation on leptin signaling pathway; blocking JAK2 phosphorylation and increase in hypothalamic SOCS3 expression have been clearly related with leptin resistance in obesity [64][65][66][67].…”
Section: Discussionsupporting
confidence: 89%
“…This result could explain the hyperphagia observed in adult overfed animals. In other models of programming during lactation, our group showed that leptin injections on the first 10 days of life program for hyperleptinemia when they were 30 days old, lower Ob-Rb and higher SOCS3 content in hypothalamus [63], similar to our present results for adult SL rats. As stated before, SOCS3 does an intracellular feedback regulation on leptin signaling pathway; blocking JAK2 phosphorylation and increase in hypothalamic SOCS3 expression have been clearly related with leptin resistance in obesity [64][65][66][67].…”
Section: Discussionsupporting
confidence: 89%
“…Using the same experimental model of programming, Dutra et al (18) demonstrated lower expression of OBR in hypothalamus and thyroid in leptin of 30-day-old leptin-programmed rats. In the present study, a very similar profile was found with lower expression of OBR in medulla, suggesting leptin resistance also in the periphery, similar to what we have found in the hypothalamus (38,53). It is well known that hyperleptinemia causes downregulation on OBRs, especially in the hypothalamus.…”
Section: E946supporting
confidence: 91%
“…However, different from the programming effect of hyperleptinemia during lactation (Toste et al 2006a) that was associated with hyperleptinemia and leptin resistance at adulthood, we did not find a programming effect of maternal flaxseed diet during lactation. On the other hand, neonatal leptin programming is also associated with hyperinsulinemia and hypoadiponectinemia in the adult offspring (Passos et al 2009). In this recent paper, we showed that SOCS3 (suppressor of cytokine signalling-3) may play a role in this leptin and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%